Effectiveness of health tourism application as the basis of health related recreational technology in primary school pupils’ physical education - Kashuba, V.O.; Goncharova, N.N.; Butenko, H.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to search effective methods of health tourism application in physical education of primary school age pupils. Матеріал: in the research 40 children participated, who were divided into control (9 boys and 11 girls) and experimental (10 boys and 10 girls) groups. We registered physical fitness, physical health, adaptation-reserve potentials and psychological state of primary school pupils. Results: specificities of health tourism means’ application as the basis of health-related recreational technology were determined. We found improvement of children’s health by 10%. Besides, we observed prevailing improvement of organism’s resistance to environmental unfavorable factors and indicators of psycho-emotional state. Conclusions: application of health tourism means increases organism’s functional potentials, physical health and psycho-emotional state of schoolchildren.